Jenis Ateji pada Manga Katekyo Hitman Reborn! Karya Amano Akira - Muhammad Ridwan; Nana Rahayu; Dini Budiani (Departement of Mathematics Education, 2024)
This study aims to identify the types of ateji found in the manga Katekyo Hitman Reborn!. This research employs a qualitative descriptive method with note-taking as the data collection technique and content analysis as the data analysis technique to obtain results in the form of written descriptive explanations. Data were taken from chapters 347 to 409 of the manga, with a total of 401 ateji identified. After eliminating repeated ateji, there were 100 different ateji. The types of ateji found include foreign language ateji, colloquial speech ateji, English abbreviations, pronouns, substitute terms, and special terms within the work. These findings demonstrate the diversity of ateji usage in the manga